دراسة العلاقة بين الميول التعليم النّحو إنجاز تعليم اللغة العربية - Syarifah, Ainun; Sholehan; Huda, M. Nurul; Maula, Izzatul; Lutfah, Nikmatul (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
This study aims to determine the extent of the relationship between learning which includes: visual, auditory and kinesthetic learning styles with learning achievement Arabic.